Analyzing kitchen workspace for food trucks in selected areas of Kuala Lumpur and Selangor - Abdul Rahman, Julaila; Jasmani, Ismail; Ramdan, Nuur Hafizah (2019)
This research aims to explore the various workspace of food truck kitchen focusing on those operated in Kuala Lumpur and Selangor areas. Therefore, the objective of this research is 1) to determine existing types of food trucks in selected areas and 2) to identify the workspace of kitchen for the food trucks in selected areas. Observation on physical elements of 17 food trucks were done. Data collection has been analyzed on the types of food trucks by line up analysis to categorized the type of menu served and location. The number of movements during food preparation were analyzed as well to obtain the work triangle ratio. The result showed that there are two types of food truck menu; fusion cuisine and western cuisine. The western fusion showed the highest number of movement during food preparation. The more numbers of preparation movements shows that the preparation of the meal was more complicated. This study also found that there are food truck workspace with work triangle and without work triangle. The wider work triangle in the kitchen will give a better workspace for food preparation. Most of the food trucks samples have ideal work triangle. However, many food truck samples still having safety issues such as discomfort and uncomfortable workingspace. To ensure the adequate and proper food truck kitchen working space, there is a need to improve the work triangle area, as well to consider following aspects; 1) to create bigger empty space in the middle of the kitchen, 2) maximum 2 workers, 3) plan zoning and suitable kitchen equipments 4) edequate entrance area. Due to there is still no proper business guideline for Food Truck, it is hope that these recommendation will contribute to the Food Truck Bussiness Operation Guideline under government and non-government agencies. By the enforcement of proper guideline for food truck business, the food truck vendors.